Discovered Facts Related to Thalassemia Diagnosis Using Curve Fitting, Lazy and Tree Classifier - Prasun Chakrabarti, Aditya Maheshwari (International Journal of Advanced Science and Technology, 2020)
The paper entails a novel approach towards realizing distribution of Thalassemia medical records based on Age, Gender, Weight and Haemoglobin Level. The research findings will facilitate in medical treatment and accordingly a predictive model can be framed for further optimization. Keywords: Distribution, Thalassemia, Haemoglobin,Predicative, Optimization